Culturally sensitive grief treatment and support: A scoping review - Anaïs Aeschlimann; Eva Heim; Clare Killikelly; Mariam Arafa; Andreas Maercker (Elsevier, 2024)
Objective: The goal of this scoping review was to assess the scope and nature of evidence concerning culturally sensitive grief treatment and support interventions, aiming to provide valuable insights for future research on grief intervention development. Introduction: Prolonged grief disorder (PGD), associated with adverse psychosocial outcomes, requires treatment. The norms of a person's culture influence grief expression, mourning rituals, and perspectives on death. Despite increasing interest in culturally sensitive grief interventions, a comprehensive synthesis of evidence is lacking. A scoping review was deemed fitting to address this gap. Inclusion criteria: This review included studies featuring participants experiencing clinically relevant grief and engaged in culturally sensitive psychosocial grief interventions. It included studies conducted in non-WEIRD contexts or those focusing on sociocultural (sub)groups distinct from the majority (in terms of age, religion, sexual orientation, etc). Methods: Following JBI methodology for scoping reviews, 13 databases were searched (Scopus, Embase, Cochrane, Sociological Abstracts, IBSS, PTSDpubs, PsycINFO, PsycArticles, PSYNDEX, MEDLINE, CINAHL, SocINDEX, and Web of Science). Limits included language (English and German), peer-reviewed articles and publication date (from 2000). The two-step screening process (titles and abstracts, full text) was piloted, and data were extracted and collated. Results: Eighteen studies were included, displaying diversity in geographical location, methodology, and target populations. Interventions targeted various forms of clinically relevant grief, lost relationships, and sociocultural groups. Cultural adaptation processes varied, with seven studies using a top-down approach. Sources of information for formative research involved theoretical models and empirical data, while local experts and qualitative research (e.g., key informant interviews) informed cultural adaptation. Outcome measures were diverse, with 15 studies showing significant pre-post intervention changes, while two did not. Conclusions: The review highlighted the emerging significance of culturally sensitive interventions for PGD, emphasizing the need for standardized approaches and further research. By shedding light on gaps and providing recommendations, it offers insights for future researchers in this field.